Relapsing Parvovirus B19 Infection after Intravenous Immunoglobulin in Renal Transplant Recipient: A Case Report - Nepali, Rabin; Chalise, Pawan R; Singh Shah, Dibya (Journal of Institute of Medicine Nepal, 2023)
Parvovirus B19 has special affinity to erythroid progenitor cells leading to destruction and inhibition of erythropoiesis. One of its presentations is pure red cell aplasia in patients receiving immunosuppressive medications after organ transplantation. Intravenous immunoglobulin and reduction of immunosuppressive medication has been used for treatment but the effects of IVIG may be temporary. Here we present a case of Relapsing infection due to Parvovirus B19 after IVIG in renal transplant recipient in Nepal. This case shows that in renal transplant patient presenting with anemia and low reticulocyte count, Parvovirus B19 infection should be suspected. Treatment with IVIG has good results but there may be relapse of infection.